Aloysia citriodora Palau (lemon verbena) for insomnia patients: A randomized, double‐blind, placebo‐controlled clinical trial of efficacy and safety. (19th November 2018) - Afrasiabian, Farshid; Mirabzadeh Ardakani, Mehran; Rahmani, Khaled; Azadi, Nammam Ali; Alemohammad, Zahra Banafsheh; Bidaki, Reza; Karimi, Mehrdad; Emtiazy, Majid; Hashempur, Mohammad Hashem
Abstract : Aloysia citriodora ( A. citriodora ) has a long history of traditional use for sedation and treatment of insomnia in different societies. This study was carried out to assess the efficacy of A. citriodora in patients with insomnia. One hundred patients were randomly divided into two groups of A. citriodora (total essential oil 1.66 mg/10 ml and total amount of flavonoid in terms of quercetin 3.22 mg/10 ml of the syrup) and placebo. They were advised to use 10 cc of the syrups; an hour before the bedtime for a period of 4 weeks. Participants were assessed using Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI) questionnaires at the baseline and then 2 and 4 weeks after the enrollment. Mean scores of global PSQI and its four components including sleep latency, habitual sleep efficiency, daytime dysfunction, and subjective sleep quality and also ISI score in the A. citriodora group improved significantly after 4 weeks of treatment when compared with the placebo group ( p  < 0.001, for all of them). Also, improvement of global score of PSQI and ISI was observed in the intervention group as compared with the placebo group, 2 weeks after the enrollment ( p  < 0.001). The results of this study showed that oral intake of A. citriodora can be suggested as a complementary treatment for patients with insomnia.